Reaction of signal grass (Urochloa spp.) cultivars to Pyricularia species associated with blast disease - Krug, Loane D. [UNESP]; Moreira, Suellen de S. [UNESP]; Vicentini, Samara N. C. [UNESP]; Nunes, Tiago C. [UNESP]; Gonçalves, Lucas M. de D. P. [UNESP]; Castroagudín, Vanina L. [UNESP]; Barrios, Sanzio C. L.; Ceresini, Paulo C. [UNESP] (FapUNIFESP (SciELO), 2024)
Fungi of the genus Pyricularia have a wide range of host plants and are capable of infecting more than 50 species of grasses, causing the blast disease, with damage to the ears. Species of the forage signal grass (Urochloa spp.) can be hosts of this genus of fungus and can be an important source of inoculum of the pathogen for other agricultural crops affected by blast, especially wheat. The objective of this study was to determine the reaction of nine cultivars of Urochloa to the pathogens Pyricularia oryzae Triticum lineage (PoTl), P. pennisetigena, P. urashimae, and P. grisea. The virulence of seven races of PoTl to signal grass cultivars was also evaluated. There was variation in the pathogenicity and virulence of Pyricularia species and PoTl races in different signal grass cultivars. The cultivars Ipyporã, BRS Tupi, and Xaraés were the most resistant to the different blast pathogen species and PoTl races. Therefore, it is recommended to cultivate these varieties in areas adjacent to wheat or in crop-livestock integration.
Reação de cultivares de braquiária (Urochloa spp.) à espécies de Pyricularia associadas à brusone
Keywords: Pyricularia grisea; Pyricularia oryzae Triticum lineage; Pyricularia pennisetigena; Pyricularia urashimae; Varietal resistance